2018
DOI: 10.1016/j.jaad.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Serlopitant for the treatment of chronic pruritus: Results of a randomized, multicenter, placebo-controlled phase 2 clinical trial

Abstract: Serlopitant, 1 mg and 5 mg daily, was associated with a statistically significant reduction in chronic pruritus and was well tolerated (NCT01951274).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 29 publications
2
87
1
3
Order By: Relevance
“…The antipruritic efficacy of NK1R antagonism by aprepitant or serlopitant is well documented but not yet understood. 6,21 Superficial spinal dorsal horn neurons that give rise to ascending somatosensory projections, express NK1R. 26 Blocking of NK1R in these neurons leads to suppression of chronic itch in mice and is thus speculated to represent the mechanism underlying the antipruritic effect 26 of aprepitant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antipruritic efficacy of NK1R antagonism by aprepitant or serlopitant is well documented but not yet understood. 6,21 Superficial spinal dorsal horn neurons that give rise to ascending somatosensory projections, express NK1R. 26 Blocking of NK1R in these neurons leads to suppression of chronic itch in mice and is thus speculated to represent the mechanism underlying the antipruritic effect 26 of aprepitant.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, another clinical trial with the novel NK1R antagonist serlopitant demonstrated high antipruritic effects in PN patients. 20,21 Up to now it is unclear if the antipruritic effects of NK1R antagonists result from receptor binding in the skin or the central nervous system. This study aims to investigate if there are any changes in cutaneous NK1 receptor expression, IL expression or signal cascade activation after NK1R therapy as a parameter of peripheral effects in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The antipruritic efficacy of NK1R antagonism by aprepitant or serlopitant is well documented but not yet understood . Superficial spinal dorsal horn neurons that give rise to ascending somatosensory projections, express NK1R .…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the binding of SP by systemic application of the NK1R antagonist aprepitant showed a marked reduction of itch in large series of patients with chronic pruritus including PN, but failed in a recent randomized placebo‐controlled clinical trial . However, another clinical trial with the novel NK1R antagonist serlopitant demonstrated high antipruritic effects in PN patients . Up to now it is unclear if the antipruritic effects of NK1R antagonists result from receptor binding in the skin or the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, treatment with oral antidepressants, such as mirtazapine, paroxetine and sertraline, have been recommended in patients with pruritus unresponsive to conventional treatment options, and particularly in patients with uraemic pruritus, cholestatic pruritus or paraneoplastic pruritus (21)(22)(23)(24)(25)(26)(27)(28). Other systemic treat-ment options include opioid receptor agonists and antagonists, thalidomide and neurokinin 1 receptor (NKR1) antagonists (29)(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%